PENGARUH ABSENSI FINGER PRINT DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BENGKULU KOKOH PERKASA DI KOTA BENGKULU - Meilaty Finthariasari; Deki Duwy Candra (UM. Bengkulu, 2021)
This study aims to determine the effect of Finger Print Attendance and Work Motivation on Employee Performance at PT. Bengkulu Kokoh Perkasa in Bengkulu City. This research is a quantitative study with a sample of 53 respondents. The sample used in this study is a saturated sample, where the entire population is used as a sample. The total number of questionnaires distributed was 53 questionnaires. Data collection techniques using observations and questionnaires. The collected data was then processed using the SPSS 21 data processing tool and analyzed using the classical assumption test analysis technique, multiple linear regression, the coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test, namely Y = 8,289 + 1,018X1 + 0,416X2 + e. From the results of partial hypothesis testing (T test) that Finger Print attendance has a significant positive effect on employee performance variables by 10.18%. Then for the motivation variable has a significant positive effect on employee performance by 4.16%. For the results simultaneously (F test) Finger Print attendance and motivation have a significant effect on employee performance variables, which is 81%.Keywords: Finger Print Attendance, Motivation, and Employee Performance